Dietary inorganic nitrate: From villain to hero in metabolic disease?. Issue 1 (26th August 2015) - McNally, Ben; Griffin, Julian L.; Roberts, Lee D.
Abstract : Historically, inorganic nitrate was believed to be an inert by‐product of nitric oxide (NO) metabolism that was readily excreted by the body. Studies utilising doses of nitrate far in excess of dietary and physiological sources reported potentially toxic and carcinogenic effects of the anion. However, nitrate is a significant component of our diets, with the majority of the anion coming from green leafy vegetables, which have been consistently shown to offer protection against obesity, type 2 diabetes and metabolic diseases. The discovery of a metabolic pathway in mammals, in which nitrate is reduced to NO, via nitrite, has warranted a re‐examination of the physiological role of this small molecule. Obesity, type 2 diabetes and the metabolic syndrome are associated with a decrease in NO bioavailability. Recent research suggests that the nitrate‐nitrite‐NO pathway may be harnessed as a therapeutic to supplement circulating NO concentrations, with both anti‐obesity and anti‐diabetic effects, as well as improving vascular function. In this review, we examine the key studies that have led to the re‐evaluation of the physiological function of inorganic nitrate, from toxic and carcinogenic metabolite, to a potentially important and beneficial agent in the treatment of metabolic disease.